A competing risk analysis of hormone therapy interruption in Asian women with breast cancer1. (15th December 2014) - Hsieh, Kun‐Pin; Chen, Li‐Chia; Cheung, Kwok‐Leung; Yang, Yi‐Hsin
Abstract: Purpose: This study aimed to use a competing risk approach to evaluate the probability of the occurrence of hormone therapy (HT) interruption and to assess its associated predictors in Asian women with breast cancer. Methods: This retrospective cohort study used the Taiwan Health Insurance Research Database from 2003 to 2011. Reimbursement data for women with newly diagnosed primary breast cancer were extracted. Interruption (gap ≥ 180 days) and time to first interruption of HT were identified. The probability of interruption was analysed by Kaplan–Meier (KM) method and cumulative incidence competing risk (CICR) method. Competing risk regressions were used to assess the predictors of interruption. Results: The 5‐year cumulative incidence of first HT interruption was 14% versus 13% estimated by the KM and the CICR methods, respectively. The estimated incidences from CICR method tended to be around 11% lower than KM method in various HT utilization patterns. Younger (≤50 years) age at diagnosis, switching HT and the presence of HT‐related adverse events were identified as predictors of interruption in competing risk regressions. Conclusions: The competing risk approach provided lower probabilities and estimates when investigating the incidence of first interruption than the standard survival analysis. The competing risk method, which takes into account the competing risks from cancer recurrence and death, should be considered in future analysis. In terms of improving persistence of HT, it is important to focus on patients of younger age at diagnosis, HT switching and experiencing adverse events. Copyright © 2014 John Wiley & Sons, Ltd.